Postpartum contraceptive use among pregnant women who delivered at Cipto Mangunkusumo General Hospital, Jakarta, Indonesia : A descriptive study - Junita Indarti; Lucas Christiawan; Dalri Suhartomo; Caroline Caroline; Ditha Loho (Majalah Obstetri dan Ginekologi, 2021)
HIGHLIGHT1. As maternal mortality rate (MMR) is still high, there should be ways to reduce the rate, one of which is the prevention of conception through contraceptive methods. 2. A descriptive study was conducted to all patients giving birth in a national hospital between 2016 to 2019 covering data on the patients, including age, parity, the origin of referral, and type of contraception.3. Most patients who gave birth in the hospital had postpartum contraception, especially permanent contraception and long-term contraception. ABSTRACTObjectives: The maternal mortality rate in Indonesia is one of the highest in the world at 305 out of 100.000 live birth. One of the best ways to reduce MMR is conception prevention through contraceptive methods. According to 2018 Demographic and Health Survey, Indonesia’s Contraceptive Prevalence Rate was as low as 57%, not even reaching the 2015 Millenium Development Goals target of 65%. We conducted a study on postpartum contraceptive use in Dr. Cipto Mangunkusumo National Central General Hospital (RSCM), Jakarta, Indonesia, to see the use of contraception in RSCM so that it can be an example of how contraception is used in RSCM for patients who give birth here.Materials and Methods: A descriptive study was conducted from all patients giving birth in RSCM from 2016 until 2019, data including patient data, consisting of patient age, parity, the origin of referral, and type of contraception, are input from the medical recordResults: There were 5,596 deliveries, consisting of 3,785 C-sections and 1,811 vaginal deliveries. As many as 5332 (95.3%) of subjects had postpartum contraception, 725 (13.67%) of which received tubectomy, and most of which received long-term contraceptive methods (IUD 4414 (82.78%) and implant 44 (0.82%)). As many as 1.065 subjects were more than 35 years of age, 6.2% of which did not use any postpartum contraception. As many as 984 subjects were RSCM bookcases, 6.9% of which did not use any postpartum contraception.Conclusion: Most patients giving birth in RSCM had postpartum contraception, especially permanent contraception and long-term contraception. The contraception profile in RSCM alone can neither describe nor represent the condition and distribution of contraceptive methods in Indonesia because RSCM is a national referral and medical education center whose cases are relatively more complex.